Sayed`s Theory on Quantum Entanglement and Teleportation: Innovative Controlling Parameters and Equations of Occurrence; E =β mc3 - El-Mongy, Sayed A. (JOURNAL OF ADVANCES IN PHYSICS, 2025)
Abstract Allah, the Creator, is entangled with everything in the universe. The Quantum Entanglement is neither spooky action at a distance nor science fiction. This theory introduces the parameters controlling the quantum entanglement and teleportation occurrence. A Sayed Quantum entanglement energy equation (SQEEE); E =β mc3, with variable speed, was derived to describe the quantum entanglement phenomena. The entanglement speed was found to be variable with distance and in the range from ~1x1012 to 1.318 x 1022m/s. The light speed violation is a must The Sayed quantum entanglement wavelength (SQEW) was calculated and found to be 2.487 x 10-35 m in the Planck scale. The quantum teleportation mechanism of an object from the macroscopic into the microscopic fields might take place through Sayed`s quantum teleportation tunneling (SQTT). Sayed quantum teleportation wavelength (SQTW) was derived and found to be 5.135x10-35m for Planck scale. A hypothetical case for object quantum teleportation acceleration (SQTA) was also calculated and found to be 4.738x1020 m/s2. It can be imagined that the universe (visible and invisible) is connected and entangled in the quantum scale by encrypted vibrational waves of specific wavelengths as the code of communication between all the universe web components. Sayed`s Quantum Entanglement & Teleportation Diagram (SQETD) was proposed.